Os gêneros discursivos emergentes da internet no ensino de língua portuguesa - Trajano, Maria Francileide de Oliveira (2018)
In this thesis, we approached a discursives gender inclusion that emerges from the internet on the didactic book for teaching and learning of Portuguese Language, in view of that the didactic book presents as one of the lead didactics resources of activities from the Portuguese Language teacher from High School on public school and most distributed didactic material nationally to the students. Our research presented the following inquiry: how the emergents discursives genders from the internet can be used for the Portuguese Language teaching? We direct our objective to analyse how the emergents discursives genders from the internet are worked on the didactic book: “Português: o contexto, interlocução e sentido” from the author Abaurre; Abaurre; Pontara (2013). This qualitative research is based on the theories of theoretical that enabled us to evidence the importance of the Technologies of Information and Communication for the society development and citizen formation for their insertion; the constant use of emergents discursives genders from the internet by the students of the first grade in high school and the presentation of some genders; the possibility of utilization of these genders to develop the process of learning-teaching on the Portuguese subject; the need of training the teachers on these technologics ways as an enriching way of their practices and contextualized experiences. Our methodology is characterized by a documental analysis from a didactic High School’s first year book to know if it meets the proposals of the officials documents regarding the importance of the technologies for the Portuguese Language teaching and how is made the contextualization about the use of new discursives genders on the classroom. The obtained data point to a superficial and limited presence of the emergents discursives genders of the internet on the examined collection, with proposed didactic activities only for the email gender, with centralization in discursives genders originated from the literary, journalism and advertise spheres, as well as the predominance and valorization of printed support. In this way, it could be concluded that the book did not, in general, presented any innovative proposal that would follow the social, cultural and technological changes of the current society and the emergence of the multiples possible knowledge to be constructed in the school through the discursives genders emergents from the Internet